The Public’s Perception of the An-Nadzir Exemplary Method in Carrying Out Its Preaching - Apriani; Hamiruddin; St. Nasriah (Jurnal Mercusuar, 2022)
This research aims to examine the exemplary conduct of An-Nadzir in carrying out his preaching in the Romang Lompoa Village, Bontomarannu Subdistrict, Gowa Regency, and to assess the community’s response to An-Nadzir’s exemplary behavior in conducting his preaching in the aforementioned location. The study adopts a qualitative descriptive research approach located in Romang Lompoa Village, Bontomarannu Subdistrict, Gowa Regency, utilizing the sociology of preaching and communication science approaches. The primary data sources for this research are Hamiruddin, the Chairman of RW 05 in the Romang Lompoa area, as the key informant, and additional informants from the community of Romang Lompoa Village. Secondary data sources include books, the internet, ebooks, journals, and other data that can complement the study. The data collection method involves observation, interviews, and documentation. The data analysis consists of three stages: data reduction, data presentation, and drawing conclusions. The research findings indicate that An-Nadzir’s exemplary conduct in preaching involves embodying three aspects: faith, transactions, and ethics. The community’s response to An-Nadzir’s exemplary behavior in preaching is positive, as the community welcomes his presence due to the exemplary practices, such as obedience to the commandments of Allah by promptly performing prayers. During interactions with the community, he demonstrates humility by speaking politely, maintains honesty in transactions, whether in buying and selling or in his work, and willingly assists fellow members and the community, earning him high regard among the local population.